The Welsh Marches: resilient farmers? Exploring farmers' resilience to extreme weather events in the recent past - Rebecca Griffiths (Ager. Revista de Estudios sobre Despoblación y Desarrollo Rural, 2015)
In the 21st century climate change will cause a significant increase in the frequency and intensity of extreme weather events across Europe. Investigating farmers’ resilience to extreme weather events in the past can be used to establish the inherent level of resilience farmers’ will have to respond to comparable events in the future. The Welsh Marches has experienced a range of extreme weather events including: heatwaves, flooding; prolonged rainfall; and heavy snowfall. To identify the resilience of farmers in the Marches farmers’ apparent vulnerabilities, coping capacity, social capital and adaptive capacity that have been exposed in past events are discussed. Rural isolation is identified as an exacerbating factor of farming vulnerability. Yet, this is also an apparent source of resilience as farmers are found to rely on high social capital to assist each other in emergency and challenging situations during extreme weather events. The paper concludes by indicating that more localised studies are required, situated within unique farming cultures. This will enable a more complete picture of farmers’ resilience across Europe to be established.